Fetal Valproate Syndrome with Limb Defects: An Indian Case Report. (24th November 2016) - Goyal, Manisha; Gupta, Ashok; Sharma, Manish; Mathur, Priyanshu; Bansal, Naresh
Abstract : Epilepsy is a common disorder and exposure to antiepileptic drugs during pregnancy increases the risk of teratogenicity. Older AEDs such as valproate and phenobarbital are associated with a higher risk of major malformations in the fetus than newer AEDs like lamotrigine and levetiracetam. Exposure to valproic acid during first trimester can result in fetal valproate syndrome (FVS), comprising typical facial features, developmental delay, and a variety of malformations such as neural tube defects, cardiac and genitourinary malformations, and limb defects. We are presenting an Indian case of FVS with major limb defects.